THE EFFICACY OF TWIN BLOCK AS A FUNCTIONAL APPLIANCE: AN OVERVIEW - NASHID FAREEN; MOHAMMAD KHURSHEED ALAM; MOHD FADHLI KHAMIS (International Journal of Pharma and Bio Sciences, 2015)
Functional appliance has been the topic of intension and eager to many researchers. The main objective of this review article is to create a clear conception on the effects of the Twin-block appliance and also compare its efficacy with other functional appliances. A systematic search of several electronic databases was conducted until March 2015. Human studies that used a Twin-block appliance were selected. Two authors reviewed and extracted the data independently and assessed the quality of the retrieved studies. The search strategy resulted in 4520 articles, of which 38 articles were selected finally based on the inclusion criteria. After analyzing the articles we were able to make a zest of the effect of Twin-block appliance (skeletal, dentoalveolar, soft tissue and psychological) on growing patients. The comparison of Twin-block appliance with other functional appliance was also noted. This article is motivated on understanding the influence and the efficacy of Twin-block appliance on malocclusion in different populations.